Role of Antioxidants in the Management and Treatment of Autism Spectrum: A Review of Pathways - Qumars Behfar; Simin Zeinali; Esfandiar Mashayekhy (Neurology Letters)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by impairments in communication, social interaction, and repetitive behaviors. While its precise etiology remains elusive, emerging evidence highlights the pivotal role of oxidative stress and mitochondrial dysfunction in ASD pathophysiology. Oxidative stress refers to the imbalance between reactive oxygen species (ROS) production and the body’s antioxidant defenses, leading to cellular and molecular damage. This imbalance has been implicated in neural inflammation, neurotransmitter dysregulation, and impaired neuronal connectivity observed in ASD. Antioxidants, both endogenous and exogenous, play a critical role in neutralizing ROS and mitigating oxidative stress. Various studies suggest that antioxidant therapies, such as supplementation with glutathione, N-acetylcysteine (NAC), and vitamins C and E, may have therapeutic potential in reducing ASD-associated symptoms by targeting oxidative stress pathways. Preclinical and clinical evidence also underscores their potential to modulate mitochondrial function, reduce neuroinflammation, and regulate the gut-brain axis, which is often altered in ASD. This review aims to critically evaluate the role of oxidative stress in ASD, the biological mechanisms by which antioxidants act, and the current clinical evidence supporting their use in ASD management. It will further explore specific pathways targeted by antioxidants and discuss limitations and future research directions in this emerging field. By synthesizing existing evidence, this review seeks to provide a comprehensive understanding of how antioxidants could complement existing ASD treatments.